Evidence for a Syncytial Origin of Eukaryotes from Ancestral State Reconstruction. (8th May 2021) - Skejo, Josip; Garg, Sriram G; Gould, Sven B; Hendriksen, Michael; Tria, Fernando D K; Bremer, Nico; Franjević, Damjan; Blackstone, Neil W; Martin, William F
Abstract: Modern accounts of eukaryogenesis entail an endosymbiotic encounter between an archaeal host and a proteobacterial endosymbiont, with subsequent evolution giving rise to a unicell possessing a single nucleus and mitochondria. The mononucleate state of the last eukaryotic common ancestor (LECA) is seldom, if ever, questioned, even though cells harboring multiple (syncytia, coenocytes, and polykaryons) are surprisingly common across eukaryotic supergroups. Here, we present a survey of multinucleated forms. Ancestral character state reconstruction for representatives of 106 eukaryotic taxa using 16 different possible roots and supergroup sister relationships, indicate that LECA, in addition to being mitochondriate, sexual, and meiotic, was multinucleate. LECA exhibited closed mitosis, which is the rule for modern syncytial forms, shedding light on the mechanics of its chromosome segregation. A simple mathematical model shows that within LECA's multinucleate cytosol, relationships among mitochondria and nuclei were neither one-to-one, nor one-to-many, but many-to-many, placing mitonuclear interactions and cytonuclear compatibility at the evolutionary base of eukaryotic cell origin. Within a syncytium, individual nuclei and individual mitochondria function as the initial lower-level evolutionary units of selection, as opposed to individual cells, during eukaryogenesis. Nuclei within a syncytium rescue each other's lethal mutations, thereby postponing selection for viable nuclei and cytonuclear compatibility to the generation of spores, buffering transitional bottlenecks at eukaryogenesis. The prokaryote-to-eukaryote transition is traditionally thought to have left no intermediates, yet if eukaryogenesis proceeded via a syncytial common ancestor, intermediate forms have persisted to the present throughout the eukaryotic tree as syncytia but have so far gone unrecognized.